On some extended energy of graphs and their applications - Sarkar Prosanta; Dey Arindam; Kumar Shiv; Pal Anita (Yugoslav Journal of Operations Research)
In this paper, we established a relation between the extended energy of graphs such as the first and second Zagreb energy, Randić energy, reciprocal Randić energy, and the atom-bond connectivity energy with some thermodynamic properties of benzenoid hydrocarbons. We have seen that these indices are well correlated to the boiling point (BP), Kovats retention index (RI), entropy (S), enthalpy of formation (ΔHf ), octanol-water partition coefficient (logP), and acentric factor (ω) of benzenoid hydrocarbons.